CRITICAL DISCOURSE ANALYSIS TERHADAP WACANA POLITIK PLURALIS PRANCIS : MEMPERSOALKAN SENTRAL DAN PERIFERI - Wening Udasmoro (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
The aim of this paper is to analyse the various discourse of French Ministry of Foreign Affairs augmented on its ideology of promoting pluralism in the country, which is strategically marketed through the Ministry’s magazine entitled Label. The social actors representing the ideology of the Ministry raise arguements advancing pluralism as an ideal part of France foreign policy. The discourses evolving from these actors arguments however, emphasized the dicotomic perspective of French centrality towards the others (the Southern countries) as pheriphery. The perspective of pluralism politics and the relationship between central and periphery are the focus of this article. In order to understand the underlying meaning of the arguments, Critical Discourse Analysis is used to illuminate the discourses of these actors. The analysis revealed that the ideal of pluralism although viewed as a good way in trying to position other countries as in oneness as a coherent group is in fact contradictory because it creates a gap or distinction between France considered as central and other countries as in the periphery